A comparative study between abdominal plain radiography and ultrasonography in non-traumatic acute abdominal emergencies in tertiary care hospital - Gathwal, Chiranjeev Kumar; Gathwal, Monika B.; Garg, Shreya; Kumari, Yogita; Singh, Kulvinder (International Journal of Research in Medical Sciences, 2016)
Background: Acute abdomen is a loose term frequently used to describe the acute abdominal pain in a subgroup of patients who are seriously ill developing suddenly, over a period of several hours or few days. Methods: It was a prospective comparative study between abdominal plain radiography and ultrasonography in non-traumatic acute abdominal emergencies in Tertiary Care Hospital. Results: All the included patients (140) were imaged with abdominal X-rays series (AAS) and Ultrasonography (US) by different blinded radiologists without conveying results to either. Final diagnosis was made on the basis of clinical findings / laboratory or biochemical findings /radiological evaluation /therapeutic response / operative findings / histopathological examination. The entire data was collected, recorded and statistically analyzed as per objectives. GIT system was most commonly involved, in 75/140 cases (53.57%). Most common diagnoses were acute appendicitis, KUB calculus disease and acute cholecystitis seen in 32/140 (22.86%), 24/140 (17.14%) and 21 (15%) cases respectively. US supersedes Provisional clinical diagnosis and Radiographic evaluation in diagnosing acute abdominal conditions with Sensitivity, Positive Predictive Value, False positive rate, False Negative rate and Diagnostic Accuracy as 90.71, 100, 0 ,9.28 and 90.71 percent respectively. Conclusions: We concluded that Plain X rays can be used as screening modality in the diagnosis of acute abdominal emergencies; however ultrasound examination is cheaper, non-invasive, quick, reliable and highly accurate modality in diagnosing the exact cause of pain and its origin in a patient presenting with an acute abdomen and thus helps the physician or surgeon to plan the timely management.